Effect of Surgical and N95 Masks on Sound Pressure Level and Listening Comprehension of Fricative Sounds - Maeda, Hitomi; Fukushige, Mami; Matsumoto, Chiharu (Journal of Japan Society of Nursing Research, 2024)
Objective: This study elucidates the effects of wearing different types of masks on sound pressure level and listening comprehension of fricative sounds. Methods: The effects of wearing no mask, surgical masks, and N95 masks were compared among subjects of both sexes in their 20s. Using Praat software, the sound pressure level (dB) was analyzed. Furthermore, the number of instances of mishearing among 15 VCV words were analyzed by focusing on fricative sounds. Results: Wearing a mask significantly attenuated the sound pressure level at high frequencies (p‹.05). The N95 mask resulted in the highest number of mishearing instances. There was a significant increase in consonant mishearing when wearing a mask (p‹.01). Tendencies for voiced sounds to become voiceless, and mishearing between the same tones were observed. Conclusions: The effects of wearing a mask were found to be more pronounced at high frequencies where consonants are typically distributed, attenuating sound pressure levels and causing mishearing. Furthermore, the effects on sound pressure level and mishearing were more significant when wearing N95 masks than surgical masks.